Trapping social wasps, in apple orchards and vineyards with synthetic volatiles and live yeast cultures in Scania, Scandinavia - Dörre, Malin Iris (SLU/Dept. of Biosystems and Technology (from 130101), 2015)
Social wasps (Hymenoptera, Vespinae) foraging for carbohydrate nutrients are a major pest, particularly in berry and fruit orchards. The identification of volatile attractants for social wasp management is accordingly an urgent research challenge. Overripe fruit and fermenting sweet baits are since long known to attract wasps. Several synthetic compounds mimicking these food sources have been developed. However, yeast volatiles, signalling fermenting fruit are still incompletely known. For the first time five, synthetic compounds and five live yeast strains were evaluated as attractants for social wasps in orchards and vineyards in Scania, Scandinavia. When blended with acetic acid, either 2-‐methylpropan-‐1-‐ol, 2-‐methylbutan-‐1-‐ol, 3-‐methylbutan-‐1-‐ol or 2-‐methylpropan-‐2-‐ol strongly attracted two social wasps, Vespula germanica and V. vulgaris. Single compounds attracted significantly fewer insects. Heptyl butanoate as a single test compound or blended with acetic acid was not attractive to social wasps. In addition to synthetic chemicals, five yeast strains known to be associated with or attractive to various insects were tested. Liquid medium with fermenting Metschnikowia andauensis, M. chrysoperlae, M. pulcherrima, Saccharomyces sp., or Cryptococcus sp. strongly attracted V. germanica and V. vulgaris.